DFT Study of the Spin-Forbidden Reaction of N2O with CO Catalysed by Y+ Ions. (February 2017) - Tong, Yongchun; Wang, Qingyun; Xu, Xinjian; Wang, Yongcheng
The mechanism of the cyclic reaction N2 O(X 1 Σ + ) + CO( 1 Σ + ) → N2 (X 1 Σg + ) + CO2 ( 1 Σg + ) catalysed by Y + ions has been investigated on both singlet and triplet potential energy surfaces. The reactions were investigated by means of the relativistic effective core potential together with the Stuttgart basis sets on Y and the UB3LYP/6-311G** level of theory on non-metal atoms. The crossings involved between the singlet and triplet energy surfaces have been investigated by means of the intrinsic reaction coordinate approach used by Yoshizawa et al. Furthermore, both steps of the reaction are exothermic and the overall reaction is exothermic by 361.12 kJ mol −1 .